Improving Supply Chain Performance with Green Warehouse, Logistics and Green Supply Chain Management - Syahfitria, Syaffaa Azzahra; Rumagit, Riyo Prasetyo; Maemunah, Siti; Hamdi, Ahmad (Institut Transportasi dan Logistik Trisakti, 2023)
The research aims to determine the effect of Green Warehouse, Logistics, and Green Supply Chain Management on Supply Chain Performance. The method used is quantitative, by share questionnaires to 100 respondents. Smart PLS software was used to evaluate the collected data. This research shows that implementing Green Warehouse significantly improves green supply chain management. This study found that the most dominant green warehouse is minimizing warehouse waste and ensuring waste disposal is managed appropriately. Logistics activities support efficiency and synergy in minimizing transportation pollution from the warehouse in shipping goods to consumers. Green Supply Chain Management (GSCM) helps improve supply chain performance by implementing environmentally friendly activities, encompassing aspects such as product design, procurement and choice of materials, production process, and ultimate delivery of the final product to customers.